2007
DOI: 10.1158/1078-0432.ccr-06-2525
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signature Predicts Recurrence in Lung Adenocarcinoma

Abstract: Purpose: Improving outcomes for early-stage lung cancer is a major research focus at present because a significant proportion of stage I patients develop recurrent disease within 5 years of curative-intent lung resection. Within tumor stage groups, conventional prognostic indicators currently fail to predict relapse accurately. Experimental Design: To identify a gene signature predictive of recurrence in primary lung adenocarcinoma, we analyzed gene expression profiles in a training set of 48 node-negative tum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 39 publications
1
69
0
Order By: Relevance
“…Previous studies have described prognostic gene expression signatures with varying discriminating prognostic power in independent datasets (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(27)(28)(29)(30)(31). A clinical relevance of single genes included in these signatures has not yet been shown, and assays dependent on fresh-frozen tissue are difficult to introduce into routine diagnostics (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have described prognostic gene expression signatures with varying discriminating prognostic power in independent datasets (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(27)(28)(29)(30)(31). A clinical relevance of single genes included in these signatures has not yet been shown, and assays dependent on fresh-frozen tissue are difficult to introduce into routine diagnostics (18).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17]. However, a recent review critically evaluated the suggested signatures and concluded that in general they do not provide additional prognostic information compared with traditional clinical parameters (18).…”
Section: Introductionmentioning
confidence: 99%
“…However, cancer cells are thought to be capable of surviving in spite of such constraints, which conceivably leads to disease progression and ultimately confers poor prognosis in affected patients. A number of studies have aimed at identifying a list of genes related to lung cancer prognosis (2,3,10,(18)(19)(20)(21); however, criticism is frequently raised noting that the gene lists used in such prognosis prediction classifiers have minimal overlaps and provide little biological insight into the underlying mechanisms. In a related study, Bild and colleagues analyzed artificially generated cells with overexpression of various oncogenes in vitro and identified oncogenic pathway signatures with a potential to separate lung cancer patients into subgroups in relation to outcome, including drug sensitivity (22).…”
Section: Discussionmentioning
confidence: 99%
“…Despite potentially curative surgery, f40% of patients will relapse within 5 years (2). Genomic profiling of NSCLC has recently provided insight into predicting the prognosis of patients with this disease (3)(4)(5)(6)(7)(8). These classifiers can contain up to several hundred genes for the identification of patients with early-stage NSCLC, who might benefit from chemotherapy in addition to surgical resection.…”
Section: Introductionmentioning
confidence: 99%